Tunable Electrochemical Grafting of Diazonium for Highly Sensitive Impedimetric DNA Sensor. Issue 8 (4th May 2020) - Kang, Su Jin; Kim, Suseong; Lee, Kyuhong; Shin, Ik-Soo; Kim, Yang-Rae
Abstract : The development of a simple, rapid, and reliable method for detecting the virus at very low levels is therefore an important health objective. To that end, a gold surface was electrochemically modified by reducing 4-nitrobenzenediazonium tetrafluoroborate. The rate of radical formation and its polymerization were significantly affected by the reaction temperature, the concentration of the diazonium precursor solution, the number of cyclic voltammetry cycles, and the scan rate. The nitro functional group was subsequently electrochemically converted into the corresponding amine. In order to detect target DNA related to dengue virus, glutaraldehyde was used to link probe DNA to the amino functional group, after which the immobilized probe DNA was hybridized with various concentrations of target DNA. Ferri/ferrocyanide signals during each step in the overall transformation, including diazonium modification, reduction to the amine, probe DNA immobilization, and target DNA hybridization, were monitored by cyclic voltammetry and electrochemical impedance spectroscopy. We finally investigated the quantitative relationship between the change in charge-transfer resistance in response to target DNA hybridization and its concentration. This sensor responded linearly in the 100 pM to 1 nM concentration range, and its detection limit was determined to be 40.6 pM.